Hormonal modulation of reproduction in Polistes fuscatus social wasps: Dual functions in both ovary development and sexual receptivity. (January 2020) - Walton, Alexander; Tumulty, James P.; Toth, Amy L.; Sheehan, Michael J.
Graphical abstract: Highlights: JH treatment increased female sexual receptivity in P. fuscatus paper wasps. JH also increased ovarian development and JH decreased long term survival. JH is important for regulating mating even when temporally separated from egg-laying. Abstract: Hormones are often major regulators of complex behaviors, such as mating and reproduction. In insects, juvenile hormone (JH) is integral to many components of reproductive physiology and behavior, but its role in female sexual receptivity is not well understood. To investigate the influence of JH on receptivity, we utilized the social wasp Polistes fuscatus. In Polistes, mating behavior is temporally separated from other components of reproduction, which allows for examination of the physiology and behavior of mating, disentangled from fertilization and egg-laying. We reared virgin gynes (reproductive females) in the lab and divided them into four groups, in which gynes received multiple topical treatments of either 20 μg, 10 μg, 5 μg, or 0 μg of the JH analog methoprene. Gynes were then placed in petri dishes with 2 unrelated males and we recorded attempted and successful mating. Additionally, we measured gyne ovarian development and survival in each group. We found that methoprene increased both sexual receptivity and ovarian development, but was associated with a decrease in long-term survival. Receptivity increased linearly as methoprene treatment increased, but the effect of methoprene on ovarian development was independent of dose. These results demonstrate the importance of JH in sexual receptivity and mating behavior. We argue that the relatively understudied Polistes gyne has potential as a model for mating and reproduction, and for the internal and external regulation of this complex behavior.